Identification of the Signature Associated With m6A RNA Methylation Regulators and m6A-Related Genes and Construction of the Risk Score for Prognostication in Early-Stage Lung Adenocarcinoma - Guo, Bingzhou; Zhang, Hongliang; Wang, Jinliang; Wu, Rilige; Zhang, Junyan; Zhang, Qiqin; Xu, Lu; Shen, Ming; Zhang, Zhibo; Gu, Fangyan; Zeng, Weiliang; Jia, Xiaodong; et al. (Frontiers in Genetics, 2021)
Background: N6-methyladenosine (m6A) RNA modification is vital for cancer patients, because methylation can alter gene expression and even affect some functional modification. In our study, we aimed to analyze m6A RNA methylation regulators and m6A-related genes to understand the prognosis of early lung adenocarcinoma. Methods: The relevant datasets which were utilized to analyze 21 m6A RNA methylation regulators and 5486 m6A-related genes in m6Avar. Univariate cox regression analysis, random survival forest analysis, Kaplan-Meier analysis, Chi-square analysis, STRING and multivariate cox analysis were carried out on the datasets, and a risk prognostic model based on three feature genes was constructed. Results: Respectively, we treated GSE31210 (n=226) as the training set, GSE50081 (n=128) and TCGA data (n=400) as test set. By performing univariable cox regression analysis and random survival forest algorithm in the training group, 218 genes were significance and three prognosis related genes (ZCRB1, ADH1C and YTHDC2) were screened out, which could divide LUAD patients into low and high risk group (P < 0.0001). The predictive efficacy of model was confirmed in the test group GSE50081 (P = 0.0018) and TCGA datasets (P = 0.014). Multiariable cox manifested that the three-gene signature was an independent risk factor in LUAD. Further, genes in the signature were also externally validated using online database. Moreover, YTHDC2 was not only the important gene in the risk score model but also played a vital role of readers in m6A methylation. Conclusion: The findings of this study suggested that associated with m6A RNA methylation regulators and m6A-related genes, three-gene signature was a reliable prognostic indicator for LUAD patients, indicating a clinical application prospect to serve as a potential therapeutic target.